The role of Bank Negara Malaysia in limiting imprudent consumption - Musa, Muhammad Adli (IIUM Press, 2015)
This study identifies the role that Bank Negara Malaysia plays in regulating imprudent consumption. In doing so, the author reviews the Guidelines on Responsible Financing introduced by the Bank in 2012 to regulate the consumer credit market. Since consumers are highly dependent on credit to purchase what they desire, the Bank tightened lending procedures. The author also argues that despite the claimed ethical superiority of Islamic finance, there is no apparent difference when it comes to providing loans (or rather financing) to consumers. The findings of this study suggest that such procedures reduced the growth of household borrowing and consumer loans/ financing. As such, the study concludes that Bank Negara Malaysia has an effective role to play in limiting the negative effects of imprudent consumption.